Expression analysis of HSP70 genes in the psychrophilic yeast glaciozyma antarctica PI12 as biomarkers for thermal stress during heat waves - Nur Athirah Yusof; Jennifer charles labo; Wan Nur Shuhaida Wan Mahadi; Makdi Masnoddin; Hyun Park; Clemente Michael Vui Ling Wong (Polish Academic Science Committee Polar Research, 2024)
Heat shock proteins 70 (Hsp70) are potential thermal stress markers as they play a pivotal role in safeguarding cells against heat shock-induced damage. The Hsp70s are present in several variants with each containing its peculiar importance due to their specific functions such as cell protection during elevated thermal stress. The present investigation evaluated the gene expression profiles of all Hsp70 genes in Glaciozyma antarctica PI12 during a heat wave condition. In this study, we exposed G. antarctica PI12 cells to a realistic heat wave to understand the impacts of the extraordinary, unprecedented heat waves that hit Antarctica at nearly 40°C above the average in 2022. The experiment was carried out through eight days where cells were exposed gradually at 0, 2, 4, 8, 12, 16, 20, 25 and 30°C. The gene expression profiles were obtained during the simulated heat wave along with non-stressed control treatments by real-time PCR. Out of the six Hsp70 genes in G. antarctica PI12, five were expressed under the conditions tested. Among the expressed genes, gahsp70-1, gahsp70-5, and gahsp70-6 showed significant upregulation. Specifically, their expression levels increased by five- to eightfold after exposure to heat shock at 4°C. Gene expression patterns at 20°C and 30°C also showed induction with the highest at 3.6 folds and 5.8 folds, respectively. These results indicate that the expression of Hsp70 genes in G. antarctica PI12 was inducible under thermal stress, indicating their importance in cells during the heat waves. These results conclude that the gene expression patterns of Hsp70 during heat waves contribute vital information on thermal adaptation in the Antarctic marine ecosystem under climate stress.